High-entropy doped manganese base oxides and their preparation methods, sodium-ion battery cathode materials and batteries

By introducing high-entropy doped manganese-based layered oxides into the positive electrode material of sodium ion battery, the problems of cycle stability and insufficient capacity are solved, and the electrochemical performance of sodium ion battery is significantly improved.

CN116062807BActive Publication Date: 2024-12-24BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310267446.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2024-12-24
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

The cycle stability and discharge specific capacity of the positive electrode material of sodium ion battery are insufficient, making it difficult to meet the practical application needs.

Method used

By introducing more than five low-content metal elements into the NaxMnO2 lattice for high entropy doping, a high-entropy doped manganese base layered oxide is formed, which is used for the positive electrode material of sodium ion battery to improve its cycle stability and rate performance.

Benefits of technology

The excellent cycle stability and magnification characteristics of the positive electrode material of sodium ion battery are achieved, and the capacity retention ability and electrochemical performance are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116062807B_ABST
    Figure CN116062807B_ABST
Patent Text Reader

Abstract

The invention discloses a high entropy doped manganese-based layered oxide and a preparation method thereof, a positive electrode material for a sodium ion battery and a battery, wherein the chemical formula of the high entropy doped manganese-based layered oxide is: Na x Mn y M z O2, wherein Na represents sodium, Mn represents manganese, and M represents a doping element, wherein the doping element is selected from five or more metal elements different from sodium and manganese in the third to fifth periods of the periodic table, 0.6≤x≤1, 0.8≤y<1, 0<z≤0.2, y+z=1. The present invention achieves high entropy doping with five or more low-content metal elements to obtain a new type of high entropy doped manganese-based hierarchical oxide, which is used as a positive electrode material for sodium ion batteries, and the results show that it exhibits electrochemical characteristics of excellent rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a high entropy doped manganese-based layered oxide and a preparation method thereof, a sodium ion battery positive electrode material and a battery. Background Art

[0002] With the continuous expansion of the new energy vehicle market and the continuous increase in the scale of power industries such as wind power and photovoltaics, the demand for large-scale energy storage devices is also increasing. Lithium-ion batteries have become the first choice for wide application in various fields due to their excellent electrochemical properties and mature preparation technology. However, due to the scarcity and local abundance of lithium resources, many countries are short of lithium resources and the price has increased sharply, which has seriously restricted the application of lithium-ion batteries in the field of large-scale energy storage.

[0003] Sodium-ion batteries have become a candidate to replace lithium-ion batteries due to their extremely abundant raw material reserves, low price, and better safety performance. They are very suitable for large-scale energy storage devices and have attracted extensive research from researchers at home and abroad. However, the low capacity, poor cycle performance and low energy density of sodium-ion battery cathode materials have become the main reasons limiting the widespread application of sodium-ion batteries. Therefore, the development of a sodium-ion battery cathode material with low cost, high capacity, high energy density and good cycle stability is of great significance to the widespread application of sodium-ion batteries.

[0004] Among the positive electrode materials of sodium ion batteries, layered oxides have become the most likely positive electrode materials for sodium ion batteries to be put into practical application due to their higher specific capacity and similar structure to lithium ion battery positive electrode materials. In order to optimize the cycle stability of layered oxide positive electrode materials, researchers mainly adopted the strategy of element doping and replacement. For example, Prakash et al. (Chem. Mater. 2012, 24, 1846-1853) prepared NaNi by Co doping. 1 / 3 Mn 1 / 3 Co 1 / 3 O2 positive electrode material, although it improves the cycle stability to a certain extent, the rate performance of the positive electrode material is poor and it is difficult to adapt to the needs of fast charging; Yan et al. (Journal of Advanced Ceramics.2022,11,158-171) prepared a medium-entropy layered oxide Na 2 / 3 Ni 1 / 3 Mn 1 / 3 Fe 1 / 4 Al 1 / 12 O2, the electrode material has a high capacity and good rate performance, but the cycle stability needs to be improved; CN112467119A discloses a high entropy layered oxide positive electrode material Na(Fe(1-x) / 5 Co (1-x) / 5 Ni (1-x) / 5 Sn (1-x) / 5 Ti (1-x) / 5 )Li x O2, because its various elements are added in equal proportions, although the positive electrode material has good cycle stability, the capacity is extremely low and cannot meet practical applications;

[0005] Although the cycle performance of layered oxide positive electrode materials can be improved by doping and replacing a single or a few elements, the cycle stability and discharge specific capacity of the sodium ion battery positive electrode materials prepared by the above scheme still do not meet the requirements of practical applications, and the preparation method of layered oxide positive electrode materials needs to be further optimized. Summary of the invention

[0006] The present invention aims at the technical problem that the cycle stability of the positive electrode material of the sodium ion battery is poor, and proposes a method of preparing a positive electrode material of the sodium ion battery by adding five or more low-content metal elements to the Na x A new type of high entropy doped manganese-based layered oxide was obtained by forming a high entropy doping technology in the MnO2 lattice, and the high entropy doped manganese-based layered oxide was used as a positive electrode material for sodium ion batteries. The results showed that high entropy doping can improve the Na x The stability of the MnO2 lattice shows excellent cycle stability and rate characteristics as a positive electrode material for sodium ion batteries.

[0007] The first aspect of the present invention provides a sodium ion battery positive electrode material, that is, a high entropy doped manganese-based layered oxide, the high entropy doped manganese-based layered oxide, the chemical formula is: Na x Mn y M z O2, wherein Na represents sodium element, Mn represents manganese element, and M represents a doping element, wherein the doping element is selected from five or more metal elements other than sodium (Na) and manganese (Mn) in the third to fifth periods of the periodic table; 0.6≤x≤1, 0.8≤y<1, 0<z≤0.2, y+z=1.

[0008] In some embodiments, the doping element (M) is selected from five or more elements of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu), titanium (Ti), magnesium (Mg), zinc (Zn), calcium (Ca), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), antimony (Sb), and aluminum (Al). The metal elements selected from the doping elements in the present invention include transition metal elements.

[0009] In some embodiments, the doping elements (M) include: at least 1 to 3 metal elements selected from the fifth period, and at least 2 to 4 metal elements selected from the third period and / or the fourth period;

[0010] In some embodiments, the metal elements of the fifth period are selected from zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), and antimony (Sb); the metal elements of the third period are selected from magnesium (Mg) and aluminum (Al); the metal elements of the fourth period are selected from calcium (Ca), titanium (Ti), vanadium (V), chromium (Cr), nickel (Ni), iron (Fe), cobalt (Co), copper (Cu), and zinc (Zn).

[0011] In some embodiments, the types of doping elements in the high entropy doped manganese-based layered oxide are five or six, and the chemical formula thereof is expressed as follows: Na x Mn y (M 1a M 2b M 3c M 4d M 5e M 6f )O2, M1, M2, M3, M4, M5, M6 represent different doping elements, 0<a≤0.05, 0<b≤0.05, 0<c≤0.05, 0<d≤0.05, 0<e≤0.05, 0≤f≤0.05.

[0012] In some embodiments, in the above chemical formula, 0<a≤0.04, 0<b≤0.04, 0<c≤0.04, 0<d≤0.04, 0<e≤0.04, and 0≤f≤0.04.

[0013] In some embodiments, in the above chemical formula, 0<a≤0.03, 0<b≤0.03, 0<c≤0.03, 0<d≤0.03, 0<e≤0.03, and 0≤f≤0.03.

[0014] In some embodiments, in the above chemical formula, 0<a≤0.02, 0<b≤0.02, 0<c≤0.02, 0<d≤0.02, 0<e≤0.02, and 0≤f≤0.02.

[0015] In some embodiments, in the above chemical formula, the values ​​of at least four of a, b, c, d, e, and f are less than or equal to 0.02 and greater than 0.

[0016] In some embodiments, the doping element (M) is selected from iron (Fe), nickel (Ni), copper (Cu), titanium (Ti), magnesium (Mg), zinc (Zn), antimony (Sb), tin (Sn), zirconium (Zr), aluminum (Al), and niobium (Nb).

[0017] In some embodiments, the high entropy doped layered oxide is a P2 / O′3 dual phase, or an O′3 phase.

[0018] In some embodiments, the XRD diffraction pattern of the high entropy doped layered manganese-based oxide includes P2 phase diffraction peaks (002) (004) (100) (102); and / or, O′3 phase diffraction peaks (001) (002) (200) (-111) (-202) (111).

[0019] The second aspect of the present invention provides a method for preparing the above-mentioned high-entropy doped manganese-based layered oxide, the steps comprising: weighing sodium salt and manganese oxide in corresponding molar ratios according to the chemical formula of the high-entropy doped manganese-based layered oxide, and the oxide of the doping element, mixing them to obtain a mixed powder; pressing the mixed powder to obtain a pressed block; and sintering the block.

[0020] In some embodiments, the sodium salt is selected from one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium citrate (C6H5Na3O7), sodium nitrate (NaNO3), and sodium hydroxide (NaOH).

[0021] In some embodiments, the mixing process includes ball milling, wherein the ball-to-material mass ratio is (5-20):1, the ball milling speed is 300 to 600 r / min, and the ball milling time is 3 to 24 h.

[0022] In some embodiments, in the above-mentioned pressing process, the steps more specifically include: loading the mixed powder into a mold, and pressing and molding it under pressure, and the pressing pressure is 5 to 30 MPa.

[0023] In some embodiments, in the above sintering process, the sintering temperature is between 500 and 1100° C., the heating rate is between 3 and 20° C. / min, and the sintering time is between 1 and 24 hours.

[0024] A third aspect of the present invention provides a sodium ion battery positive electrode material, which comprises: the above-mentioned high entropy doped manganese-based layered oxide, or the high entropy doped manganese-based layered oxide obtained by the above-mentioned preparation method.

[0025] A fourth aspect of the present invention provides an electrode sheet, which includes the above-mentioned high-entropy doped manganese-based layered oxide, or the high-entropy doped manganese-based layered oxide obtained by the above-mentioned preparation method.

[0026] A fifth aspect of the present invention provides a sodium ion battery, comprising the above-mentioned sodium ion battery positive electrode material.

[0027] The sixth aspect of the present invention provides an electrical device, comprising the above-mentioned sodium ion battery. These electrical devices include electric vehicles, electric bicycles, energy storage power stations, electronic appliances, etc.

[0028] Compared with the prior art, the present invention uses a manganese-based layered oxide positive electrode material Na x MnO2 is used as the matrix, and high entropy doping is achieved through more than five low-content metal elements to obtain a new type of high entropy doped manganese-based layered oxide, in which each doping element can form a joint lattice by sharing the same atomic site, causing a certain degree of lattice distortion. The disordered arrangement of each doping element increases the mixing entropy of the material and improves the structural stability of the material. The high entropy doped manganese-based layered oxide is used as the positive electrode material of sodium ion batteries, and the results show that it exhibits excellent electrochemical characteristics of rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The P2 / O′3 dual-phase high entropy doped manganese-based layered oxide NaMn in Example 1 of the present invention 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )XRD spectrum of O2.

[0030] Figure 2 The P2 / O′3 dual-phase high entropy doped manganese-based layered oxide NaMn in Example 1 of the present invention 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )SEM photograph of O2 (a) and the distribution diagrams of the elements Na, Mn, Ni, Fe, Cu, Sb and Zn therein (b~h).

[0031] Figure 3 This is the first charge and discharge curve of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as the positive electrode material of a sodium ion battery in Example 1 of the present invention.

[0032] Figure 4 The test results of the cycle performance of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as the positive electrode material of the sodium ion battery in Example 1 of the present invention.

[0033] Figure 5 The results of rate performance test of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as a positive electrode material for a sodium ion battery in Example 1 of the present invention.

[0034] Figure 6This is a comparison of the XRD spectra of the high entropy doped manganese-based layered oxide as a positive electrode material after 100 cycles with the initial state in Example 1 of the present invention.

[0035] Figure 7 The P2 / O′3 dual-phase high entropy doped manganese-based layered oxide NaMn in Example 2 of the present invention 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )XRD spectrum of O2.

[0036] Figure 8 The P2 / O′3 dual-phase high entropy doped manganese-based layered oxide NaMn in Example 2 of the present invention 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )SEM photograph of O2 (a) and element distribution diagram of each element Na, Mn, Ni, Fe, Cu, Sb and Zn (b~h).

[0037] Fig. 9 This is the first charge and discharge curve of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as the positive electrode material of a sodium ion battery in Example 2 of the present invention.

[0038] Fig.10 The test results of the cycle performance of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as the positive electrode material of the sodium ion battery in Example 2 of the present invention.

[0039] Fig.11 The results of rate performance test of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as a positive electrode material for a sodium ion battery in Example 2 of the present invention.

[0040] Fig.12 This is a comparison of the XRD spectra of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as the positive electrode material after 100 cycles with the initial state in Example 2 of the present invention.

[0041] Fig.13 3 is the XRD spectrum of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide in Example 3 of the present invention.

[0042] Fig.14 This is a SEM photograph of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide in Example 3 of the present invention.

[0043] Fig.15The results of the cycling performance tests of sodium ion batteries using different P2 / O′3 dual-phase high entropy doped manganese-based layered oxides as positive electrode materials in Example 3 of the present invention are compared. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is described below by specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0045] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0046] The preparation method of the positive electrode sheet of a sodium ion battery described in the present invention comprises the following steps: 1) mixing a positive electrode material of a sodium ion battery (in the present invention, a high entropy doped manganese-based layered oxide) with a conductive agent (Super P) and a binder (PVDF) in a mass ratio of 7:2:1 and grinding for 10 minutes, then adding an appropriate amount of N-methylpyrrolidone (NMP) and grinding for another 20 minutes to prepare a mixed slurry; 2) coating the obtained mixed slurry on an aluminum foil disc with a diameter of 12 mm, with a loading amount of 1.5 mg / cm 2 , and then put the coated electrode sheet into a vacuum oven at 80°C and dry it for 12 hours to obtain the positive electrode sheet.

[0047] Using the same method, the high entropy doped manganese-based layered oxides were replaced by other layered oxides, such as NaMnO2, a small amount of doped layered oxide NaMn 0.8 Ni 0.2 O2、NaMn 0.89 Ni 0.04 Fe 0.04 Sb 0.03 O2、NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06 O2, and obtain a comparative positive electrode sheet.

[0048] The assembly method of the sodium ion battery recorded in the present invention comprises the following steps: using a metallic sodium sheet as a negative electrode and the positive electrode sheet prepared as above as a positive electrode, making a CR2032 button battery in an argon glove box, wherein a glass fiber diaphragm is used as a diaphragm, an electrolyte is used as a 1M NaClO4 solution, and the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, and contains 2% by volume of fluoroethylene carbonate (FEC).

[0049] The charge and discharge performance test of the sodium ion battery in the present invention is carried out on a Land BT2000 battery test system, the test temperature is room temperature, and the test voltage range is 2.0-4.0V.

[0050] The Na in the high entropy doped layered oxide of the present invention x Mn y M z O2, high entropy doping is achieved by more than five low-content metal elements. The selection of the types of these doping elements is the key technical point for forming high entropy doping. The atomic sizes of doped metals with different high entropy and the selection of metal elements with staggered atomic sizes are conducive to the formation of a stable high entropy doped lattice phase. Therefore, the doping elements are preferably matched by metal elements of the third and / or fourth period with metal elements of the fifth period, thereby obtaining a stable high entropy doped layered oxide.

[0051] In some embodiments, the doping element M is selected from one to three of the metal elements zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tin (Sn), and antimony (Sb) in the fifth period of the periodic table; and / or, the doping element M is selected from two to four of the metal elements magnesium (Mg), aluminum (Al), calcium Ca, titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), cobalt (Co), copper (Cu), and zinc (Zn) in the third and fourth periods of the periodic table.

[0052] Example 1

[0053] This embodiment provides a high entropy doped manganese-based layered oxide NaMn 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )O2 and its preparation method. The preparation method comprises the steps of:

[0054] S01: According to the chemical formula of high entropy doped manganese-based layered oxide, the corresponding molar ratio of Na2CO3 and MnO2 and the oxide powder of the doping element are weighed, and ball milling is performed to obtain a mixed powder; specifically, according to the molar ratio of 0.5:0.89:0.02:0.01:0.02:0.015:0.02, Na2CO3, MnO2, NiO, Fe2O3, CuO, Sb2O5 and ZnO powders are weighed respectively, and placed in an agate jar, agate balls are added according to the ball-to-material mass ratio of 10:1, and then an appropriate amount of ethanol is added as a dispersant, and finally the ball mill jar is placed on a ball mill for ball milling for 4 hours. After the ball milling is completed, the ball mill jar is placed in an 80°C blast oven and dried for 10 hours to obtain a ball-milled mixed powder;

[0055] S02: pressing the mixed powder after ball milling to obtain a pressed block; specifically, placing the dried mixed powder in a circular groove mold with a diameter of 14 mm, and pressing the mixed powder under a pressure of 10 MPa to obtain a circular block with a diameter of 14 mm;

[0056] S03: sintering the block, grinding the sintered product to obtain a high entropy doped manganese-based layered oxide; specifically, placing the pressed round block into an alumina crucible, and then placing the crucible into a muffle furnace, heating to 950°C at 10°C / min, sintering in an air atmosphere for 12 hours, and cooling with the furnace, grinding and sieving the sintered block to obtain the target product NaMn 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )O2.

[0057] The XRD test results of the target product are as follows: Figure 1 As shown, it can be seen that the target product has characteristic peaks of P2 phase at 15.9°, 32°, 35.7°, 39.4°, 43.5°, and 48.9°, corresponding to the (002)(004)(100)(102)(103)(104) crystal planes, respectively. Characteristic peaks of O′3 phase appear at 16.6°, 31.7°, 33.6°, 34.4°, 36.6°, 37.7°, and 42.7°, corresponding to the (001), (-201)(002)(200)(-111)(-202)(111) crystal planes, respectively. This indicates that the target product contains both characteristic peaks of P2 phase and characteristic peaks of O′3 phase. The target product NaMn 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02)O2 is a P2 / O′3 dual-phase composite structure, among which (002)(102) corresponds to the strong diffraction peak of the P2 phase, and relatively speaking (004)(100)(103)(104) are weak diffraction peaks; (001)(111) corresponds to the strong diffraction peak of the O′3 phase, and relatively speaking (002)(200)(-111)(-202) are weak diffraction peaks. Figure 2 a shows a scanning electron microscope (SEM) photo of the target product, which shows that the target product has a micron-scale layered granular structure. Figure 2 From the element distribution diagrams b to h, it can be seen that the elements Na, Mn, Ni, Fe, Cu, Sb and Zn are evenly distributed in the target product.

[0058] This embodiment also provides a use of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide obtained as a positive electrode material for a sodium ion battery, that is, a sodium ion battery positive electrode material and a sodium ion battery are provided. Figure 3 The P2 / O′3 dual-phase high entropy doped manganese-based hierarchical oxide NaMn 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )O2 as the positive electrode material of the sodium ion battery, it can be seen that the high entropy doped manganese-based layered oxide of the present invention as the positive electrode material of the sodium ion battery has a charge and discharge capacity of 188 mAhg -1 The initial capacity and the first-cycle coulomb efficiency can reach 85%. Figure 4 The cycling performance test results of the sodium ion battery using the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide as the positive electrode material are given. It can be seen that the initial capacity of the high entropy doped manganese-based layered oxide as the positive electrode material of the sodium ion battery is comparable to that of NaMnO2 and NaMn 0.89 Ni 0.04 Fe 0.04 Sb 0.03 O2 positive electrode material equivalent (>150mAhg -1 ), but the capacity of the high entropy doped manganese-based structured oxide of the present invention has almost no decay after 100 charge and discharge cycles, and still remains at about 160 mAh g -1 , while in the comparison battery, NaMnO2 and NaMn 0.89 Ni 0.04 Fe 0.04 Sb 0.03 The capacity of the O2 cathode material shows a significant attenuation, with only about 120 mAh g remaining after 100 cycles. -1 and 130mAhg -1The results show that the high entropy doped manganese-based layered oxide of the present invention has excellent capacity retention and cycle stability as a positive electrode material for sodium ion batteries. Figure 5 ), it can also be seen that the high entropy doped manganese-based layered oxide of the present invention as a positive electrode material for sodium ion batteries has an initial capacity of up to 195 mAh g at a charge and discharge rate of 0.1C. -1 , the capacity at 0.2C is about 170mAhg -1 When the charge and discharge rate increases to 5C, it still remains at about 123mAhg -1 , compared with NaMnO2 and NaMn 0.89 Ni 0.04 Fe 0.04 Sb 0.03 O2 positive electrode material is only 80mAhg -1 and 104mAhg -1 , it can be seen that the high entropy doped manganese-based layered oxide of the present invention also exhibits excellent rate performance. The excellent rate performance is due to the material properties. High entropy doping is introduced into the layered oxide NaMnO2, and the chemical disorder and distortion produced by multiple elements will locally disrupt the site energy, thereby producing a distribution of site energy. When this distribution is wide enough so that the energies of adjacent sites overlap, ion hopping between them will be promoted. If this network of sites with similar energy permeates, the macroscopic ion diffusion will be enhanced due to disorder. In terms of material properties, it will show an enhancement in conductivity. This can be proved by first-principles calculations and experiments that the use of high entropy to introduce chemical disorder into inorganic solid electrolytes can increase ionic conductivity by several orders of magnitude, thereby reducing the overall battery resistance to improve performance.

[0059] In particular, from Figure 5 It can also be seen that when the charge-discharge rate is restored to 0.1C, the capacity of the high-entropy doped manganese-based layered oxide of the present invention can be restored to 185 mAh g -1 , while NaMnO2 and NaMn 0.89 Ni 0.04 Fe 0.04 Sb 0.03 The capacity of O2 positive electrode material is only 140mAhg -1 and 173mAhg -1 The capacity can be restored after high-rate charge and discharge, indicating that the repeated embedding and de-embedding of sodium ions in the high-entropy doped manganese-based layered oxide of the present invention does not destroy its material structure, which is related to the fact that high-entropy doping can improve the structural stability of layered oxide materials. Figure 6A comparison of the XRD spectra of the high-entropy doped manganese-based layered oxide after 100 cycles and the initial high-entropy doped manganese-based layered oxide is given. It can be seen that the high-entropy doped manganese-based layered oxide positive electrode material still maintains the original crystal form even after 100 cycles of charge and discharge, further proving its excellent structural stability.

[0060] During the sintering process, the sodium carbonate (Na2CO3) in the raw material is heated and reacts with the metal oxide under high temperature conditions to undergo a solid phase sintering reaction. In other embodiments, the sodium carbonate in the raw material can also be replaced by other sodium salts such as sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium citrate (C6H5Na3O7), sodium nitrate (NaNO3), and sodium hydroxide (NaOH). The manganese oxides in the raw material include: MnO, MnO2, Mn2O3, Mn3O4, Mn2O5, etc.; the nickel oxides in the raw material include NiO and Ni2O3, and the iron oxides in the raw material include FeO, Fe2O3 and Fe3O4.

[0061] Example 2

[0062] This embodiment provides a high entropy doped manganese-based layered oxide NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )O2 and its preparation method. The preparation method comprises the steps of:

[0063] S11: According to the chemical formula of high entropy doped manganese-based layered oxide, Na2CO3 and MnO2 in corresponding molar ratios and oxide powders of doping elements are weighed and ball-milled to obtain a mixed powder; specifically, Na2CO3, MnO2, NiO, Fe2O3, CuO, Sb2O3 and ZnO powders are weighed in a molar ratio of 0.5:0.8:0.05:0.025:0.05:0.015:0.02, respectively, and placed in an agate jar, agate balls are added according to a ball-to-material mass ratio of 10:1, and then an appropriate amount of ethanol is added as a dispersant, and finally the ball mill jar is placed on a ball mill for ball milling for 4 hours. After the ball milling is completed, the ball mill jar is placed in an 80°C blast oven and dried for 10 hours to obtain a ball-milled mixed powder;

[0064] S12: pressing the mixed powder after ball milling to obtain a pressed block; specifically, placing the dried mixed powder in a circular groove mold with a diameter of 14 mm, and pressing the mixed powder under a pressure of 10 MPa to obtain a circular block with a diameter of 14 mm;

[0065] S13: sintering the block, grinding the sintered product to obtain a high entropy doped manganese-based layered oxide; specifically, placing the pressed round block into an alumina crucible, and then placing the crucible into a muffle furnace, heating to 950°C at 10°C / min, sintering in an air atmosphere for 12 hours, and cooling with the furnace, grinding and sieving the sintered block to obtain the target product P2 / O′3 dual-phase NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )O2.

[0066] The XRD test results of the target product are as follows: Figure 7 As shown, it can be seen that the target product has characteristic peaks of P2 phase at 15.8°, 31.9°, 35.8°, 39.2°, 43.4°, and 48.7°, corresponding to the (002)(004)(100)(102)(103)(104) crystal planes, respectively. Characteristic peaks of O′3 phase appear at 16.5°, 31.8°, 33.5°, 34.3°, 36.7°, 37.6°, and 42.6°, corresponding to the (001), (-201)(002)(200)(-111)(-202)(111) crystal planes, respectively. This indicates that the target product contains both characteristic peaks of P2 phase and characteristic peaks of O′3 phase. The target product NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )O2 is a P2 / O′3 dual-phase composite structure; Figure 1 The difference is that the diffraction intensity of each crystal plane is different. Specifically, Figure 1 The characteristic peak intensity of the O′3 phase crystal plane is greater than that of the P2 phase. Figure 7 The intensity of the characteristic peak of the P2 phase crystal plane is greater than that of the O′3 phase crystal plane, indicating that the proportion of the O′3 phase in the product obtained in Example 1 is greater than that of the P2 phase, while the proportion of the O′3 phase in the product obtained in Example 2 is less than that of the P2 phase; Figure 8 a shows a scanning electron microscope (SEM) photo of the target product, which shows that the target product has a micron-scale layered granular structure. Figure 8 From the element distribution diagrams b to h, it can be seen that the elements Na, Mn, Ni, Fe, Cu, Sb and Zn are evenly distributed in the target product.

[0067] This embodiment also provides a use of the P2 / O′3 dual-phase high entropy doped manganese-based layered oxide obtained as a positive electrode material for a sodium ion battery, that is, a sodium ion battery positive electrode material and a sodium ion battery are provided. Fig. 9 The first charge and discharge curve of the sodium ion battery using the P2 / O′3 dual-phase high entropy doped manganese-based structured oxide as the positive electrode material of the sodium ion battery is given. It can be seen that the high entropy doped manganese-based structured oxide of the present invention as the positive electrode material of the sodium ion battery has a charge and discharge capacity of 156 mAh g -1 The initial capacity and the first-cycle coulomb efficiency can reach 83%.

[0068] Fig.10 The P2 / O′3 dual-phase high entropy doped manganese-based hierarchical oxide NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )O2 as the positive electrode material of the sodium ion battery cycle performance test results, it can be seen that the high entropy doped manganese-based layered oxide of the present invention as the positive electrode material of the sodium ion battery at 0.5C has an initial capacity of about 120mAhg -1 ) is slightly higher than the control sample NaMn 0.8 Ni 0.2 O2 and NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06 The capacity of the high entropy doped manganese-based layered oxide of the present invention is almost unchanged after 100 charge and discharge cycles, and remains at about 122 mAh g -1 , while in the comparison battery, NaMn 0.8 Ni 0.2 O2 and NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06 The capacity of the O2 cathode material shows a significant attenuation, with the capacity remaining at only 74 mAh g after 100 cycles. -1 and 98mAhg -1 The results show that the high entropy doped manganese-based layered oxide of the present invention has excellent capacity retention and cycle stability as a positive electrode material for sodium ion batteries. Fig.11 ), it can also be seen that the high entropy doped manganese-based layered oxide of the present invention as a positive electrode material for sodium ion batteries has an initial capacity of up to 156 mAh g at a charge and discharge rate of 0.1C. -1 , the capacity at 0.2C is about 138mAhg -1When the charge and discharge rate increases to 5C, it still remains at about 88mAhg -1 , compared with NaMn 0.8 Ni 0.2 O2 and NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06 O2 positive electrode materials are only 51mAhg -1 and 63mAhg -1 It can be seen that the high entropy doped manganese-based hierarchical oxide of the present invention exhibits excellent rate performance; in particular, when the charge-discharge rate is restored to 0.1C, the capacity of the high entropy doped manganese-based hierarchical oxide of the present invention can be restored to 152 mAh g -1 , while the comparison sample NaMn 0.8 Ni 0.2 O2 and NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06 The capacity of the O2 cathode material can only be restored to 131 mAh g -1 and 144mAhg -1 , and cannot be restored to near the initial capacity. This is related to the fact that high entropy doping elements can improve the stability of the material. It can be seen that the high entropy doped manganese-based layered oxide of the present invention is different from NaMn 0.8 Ni 0.2 O2 and NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06 Compared with O2, it also shows excellent rate high capacity performance and cycle stability. Fig.12 It can be seen from the XRD spectrum that the high-entropy doped manganese-based layered oxide positive electrode material still maintains its original crystal form after 100 cycles of charge and discharge, and has excellent structural stability.

[0069] It can be seen from the electrochemical test results of Examples 1 and 2 that the high entropy doped manganese-based layered oxide of the present invention as a positive electrode material for sodium ion batteries has better cycle stability and rate performance than undoped NaMnO2 and layered oxides doped with a small amount of elements (such as NaMn 0.8 Ni 0.2 O2、NaMn 0.89 Ni 0.04 Fe 0.04 Sb 0.03 O2、NaMn 0.8 Ni 0.07 Fe 0.07 Sb 0.06O2). This is related to the fact that high entropy doping can improve the structural stability of materials and improve electrical conductivity.

[0070] In another embodiment, after ZnO in Example 2 is replaced by MgO, other conditions remain unchanged, and NaMn is obtained by high temperature solid phase sintering. 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Mg 0.02 )O2.

[0071] By high entropy doping of manganese-based layered oxides NaMn in Examples 1 and 2 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )O2 and NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )Comparison of electrochemical performance test results of O2 as a positive electrode material for sodium ion batteries (see Figure 4 , 5 and Fig.10 and 11 ), it can also be seen that the high entropy doped manganese-based layered oxide NaMn in Example 1 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )O2 doping content is lower than that of NaMn in Example 2 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )O2, but from the perspective of specific capacity, cycle performance and rate performance, the NaMn 0.89 (Ni 0.02 Fe 0.02 Cu 0.02 Sb 0.03 Zn 0.02 )O2 is better than NaMn in Example 2 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02)O2, it can be seen that the doping content is also one of the factors affecting the manganese-based layered oxide, and the higher the doping content, the better. On the contrary, a lower doping amount is beneficial to the electrochemical performance improvement of high-entropy doped manganese-based layered oxide as a positive electrode material for sodium ion batteries. Therefore, expressed in chemical formula, high-entropy doped manganese-based layered oxide Na x Mn y (M 1a M 2b M 3c M 4d M 5e M 6f )O2, wherein 0<a≤0.05, 0<b≤0.05, 0<c≤0.05, 0<d≤0.05, 0<e≤0.05, 0≤f≤0.05; further reducing the content of doping elements, preferably, 0<a≤0.04, 0<b≤0.04, 0<c≤0.04, 0<d≤0.04, 0<e≤0.04, 0≤f≤0.04; more preferably, 0<a≤0.03, 0<b≤0.03, 0<c≤0.03, 0<d≤0.03, 0<e≤0.03, 0≤f≤0.03. In a preferred embodiment, 0<a≤0.02, 0<b≤0.02, 0<c≤0.02, 0<d≤0.02, 0<e≤0.03, 0≤f≤0.02. In another preferred embodiment, at least four values ​​of a-f are ≤0.02 and greater than 0.

[0072] Example 3

[0073] This embodiment provides another high entropy doped manganese-based layered oxide NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Ti 0.03 Zn 0.02 )O2 and a preparation method thereof, wherein the doping element is selected from the fourth period in the periodic table. The preparation method comprises the steps of:

[0074] S21: According to the chemical formula of high entropy doped manganese-based layered oxide, Na2CO3 and MnO2 in corresponding molar ratios and oxide powders of doping elements are weighed, and ball milling is performed to obtain a mixed powder; specifically, Na2CO3, MnO2, NiO, Fe2O3, CuO, TiO2 and ZnO powders are weighed according to a molar ratio of 0.5:0.8:0.05:0.025:0.05:0.015:0.02, respectively, and placed in an agate jar, agate balls are added according to a ball-to-material mass ratio of 10:1, and then an appropriate amount of ethanol is added as a dispersant, and finally the ball mill jar is placed on a ball mill for ball milling for 4 hours. After the ball milling is completed, the ball mill jar is placed in an 80°C blast oven and dried for 10 hours to obtain a ball-milled mixed powder;

[0075] S22: pressing the mixed powder after ball milling to obtain a pressed block; specifically, placing the dried mixed powder in a circular groove mold with a diameter of 14 mm, and pressing the mixed powder under a pressure of 10 MPa to obtain a circular block with a diameter of 14 mm;

[0076] S23: sintering the block, grinding the sintered product to obtain a high entropy doped manganese-based spherical oxide; specifically, placing the pressed round block into an alumina crucible, and then placing the crucible into a muffle furnace, heating to 950°C at 10°C / min, sintering in an air atmosphere for 12 hours, and cooling with the furnace, grinding and sieving the sintered block to obtain the target product P2 / O′3 dual-phase NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Ti 0.03 Zn 0.02 )O2.

[0077] The XRD test results of the target product are as follows: Fig.13 As shown, it can be seen that the target product has characteristic peaks of P2 phase at 16°, 31.8°, 35.9°, 39.1°, 43.3°, and 48.8°, corresponding to the (002)(004)(100)(102)(103)(104) crystal planes, respectively. Characteristic peaks of O′3 phase appear at 16.6°, 31.7°, 33.4°, 34.5°, 36.8°, 37.5°, and 42.4°, corresponding to the (001), (-201)(002)(200)(-111)(-202)(111) crystal planes, respectively. This indicates that the target product contains both characteristic peaks of P2 phase and characteristic peaks of O′3 phase. The target product NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Ti 0.03 Zn 0.02 )O2 is a P2 / O′3 dual-phase composite structure; Figure 1 and Figure 7 The difference is that the diffraction intensity of each crystal plane is different. Specifically, Figure 1 The characteristic peak intensity of the O′3 phase crystal plane is greater than that of the P2 phase. Figure 7 The characteristic peak intensity of the P2 phase crystal plane is greater than that of the O′3 phase crystal plane. Fig.13 The intensity of the characteristic peak of the O′3 phase crystal plane is not much different from that of the P2 phase, indicating that the proportion of the O′3 phase in the product obtained in Example 3 is similar to that of the P2 phase. Fig.14A scanning electron microscope (SEM) photograph of the target product is given, and it can be seen that the microstructure of the target product is micron-scale layered particles.

[0078] This embodiment also provides a use of the P2 / O'3 dual-phase high entropy doped manganese-based layered oxide obtained above as a positive electrode material for a sodium ion battery, that is, a positive electrode material for a sodium ion battery and a sodium ion battery are provided, and is compared with a high entropy doped layered oxide positive electrode material having different periodic doping elements.

[0079] Fig.15 The P2 / O′3 dual-phase high entropy doped manganese-based hierarchical oxide NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Ti 0.03 Zn 0.02 )O2 as the positive electrode material of the sodium ion battery cycle performance test results, it can be seen that the high entropy doped manganese-based layered oxide of the present invention as the positive electrode material of the sodium ion battery at 0.5C has an initial capacity of about 113mAhg -1 ) is lower than NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 )O2 positive electrode material (about 120mAhg -1 ) and NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Mg 0.02 )O2(about 125mAhg -1 ) positive electrode material, and the high entropy doped layered oxide of the present invention has a residual capacity of about 96 mAhg after 100 charge and discharge cycles. -1 , the capacity retention rate is only 87%, while in the comparison battery, NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Zn 0.02 ) After 100 cycles, the capacity of the O2 cathode material is still about 111 mAhg -1 , the capacity retention rate is 92%, NaMn 0.8 (Ni 0.05 Fe 0.05 Cu 0.05 Sb 0.03 Mg 0.02) The capacity retention rate of the O2 positive electrode material after 100 cycles is 98%. By comparison, it can be shown that the doping elements are preferably matched by the metal elements of the third and / or fourth period with the metal elements of the fifth period, thereby obtaining a more stable high entropy doped manganese-based layered oxide.

[0080] Example 4

[0081] Using a preparation method similar to that of Example 1, by changing the ratio of Na2CO3 and MnO2 in the raw materials and the oxide powder of the doping element, the applicant also sintered and synthesized other high entropy doped manganese-based hierarchical oxides, as shown in the following table:

[0082]

[0083]

[0084] It should be noted that the preparation method of high entropy doped manganese-based layered oxide can be further adjusted. In some embodiments, in the ball milling mixing, the ball-to-material mass ratio is (5-20): 1, the dispersant is ethanol, acetone, N-methylpyrrolidone (NMP), isopropyl alcohol (IPA) or water, the ball milling speed is 300-600r / min, and the ball milling time is 3-24h; in the pressing step, the pressure is 5-30Mpa; in the sintering step, the sintering temperature is between 500-1100°C, the heating rate is 3-20°C / min, and the sintering time is 1-24h. Specific experimental conditions can be obtained by conducting a limited number of experiments according to different material types, or in other words, more optimized experimental conditions can be obtained through a limited number of experiments.

[0085] The high entropy doped manganese-based layered oxide of the present invention is used as a positive electrode material for sodium ion batteries, preferably a P2 / O′3 dual phase. The O′3 phase manganese-based layered oxide positive electrode material has the advantages of large capacity and high cost performance. However, the kinetics of the material are slow and the volume changes dramatically during the extraction and insertion of Na ions, resulting in lower rate capability and poor cycle stability. The P2 phase layered oxide positive electrode material has a wider triangular Na ion transport channel and a lower migration energy barrier, which is beneficial to the transport of Na ions, and its phase transition energy barrier is higher, so the P2 phase layered oxide positive electrode material has high rate performance and a relatively stable structure. However, the defect of low sodium content in the P2 phase layered oxide positive electrode material is not conducive to its application in full batteries. By integrating the structurally stable P2 phase into the O′3 phase, not only can the sharp lattice strain be buffered, but also the diffusion of Na ions is enhanced, so that a structurally stable, high-rate performance P2 / O′3 dual-phase manganese-based layered oxide positive electrode material can be obtained. That is, the preferred P2 / O′3 dual-phase high-entropy doped manganese-based layered oxide of the present invention has the advantages of both P2 phase and O′3, and provides a technical solution to the technical problem that the P2 phase layered oxide positive electrode material is a low-sodium material and has serious irreversible sodium loss when used in sodium ion batteries, resulting in a reduction in the theoretical density of the battery.

[0086] It should be noted that in the steps of the preparation method of the present invention, the meaning of "corresponding molar ratio" in the present invention includes not only the stoichiometric molar ratio of each element in the chemical formula of the high entropy doped manganese-based layered oxide; 0.6 Mn 0.9 (Ni 0.02 Ti 0.02 Mg 0.02 Nb 0.02 Mo 0.02 )O2 as an example. The stoichiometric molar ratio refers to the preparation of unit mole of Na 0.6 Mn 0.9 (Ni 0.02 Ti 0.02 Mg 0.02 Nb 0.02 Mo 0.02)O2, wherein the molar ratio of each element is Na:Mn:Ni:Ti:Mg:Nb:Mo=0.6:0.9:0.02:0.02:0.02:0.02:0.02; that is, based on the ratio of the subscript values ​​of each element in the chemical formula; it also includes making appropriate increase or decrease adjustments to the stoichiometric molar ratio of one or more raw material components, and calculating the corresponding feed molar ratio of the actual feed amount of the raw material component; more specifically, the feed molar ratio after appropriate increase or decrease adjustment is 90% to 110% of the stoichiometric molar ratio; in specific implementations, the use of feed molar ratio and stoichiometric molar ratio both belong to the meaning of "corresponding molar ratio" of the present invention. In a specific embodiment, the actual feed molar ratio of Na2CO3 is 102% to 105% of the stoichiometric molar ratio, and the remaining Mn oxides and M oxides are calculated according to the stoichiometric molar ratio, and the feed amount is calculated according to the feed molar ratio and the stoichiometric molar ratio respectively.

[0087] It should be noted that the main purpose of the ball milling process in the embodiment of the present invention is to fully and evenly mix the raw materials, which is one of the mixing treatment methods; in other embodiments, other mechanical equipment that can achieve the purpose of uniform mixing can also be used, such as mechanical stirring and dispersion.

[0088] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A high entropy doped manganese-based layered oxide, characterized in that: The chemical formula of the high entropy doped manganese-based layered oxide is: Na x Mn y (M 1a M 2b M 3c M 4d M 5e M 6f )O2, wherein Na represents sodium, Mn represents manganese, M1, M2, M3, M4, M5, and M6 represent different doping elements, and 0< a ≤0.05,0< b ≤0.05,0< c ≤0.05,0< d ≤0.05,0< e ≤0.05,0≤ f ≤0.05, a + b + c + d + e + f=z, The doping element is selected from five or more metal elements other than sodium and manganese in the third to fifth periods of the periodic table; 0.6≤ x ≤1,0.8≤ y <1,0< z ≤0.2, y + z =1.

2. The high entropy doped manganese-based layered oxide according to claim 1, characterized in that: The doping elements are selected from five or more elements of iron, nickel, cobalt, copper, titanium, magnesium, zinc, calcium, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony and aluminum.

3. The high entropy doped manganese-based layered oxide according to claim 1, characterized in that: The M includes: at least 1 to 3 metal elements selected from the fifth period, and at least 2 to 4 metal elements selected from the third period and / or the fourth period.

4. The high entropy doped manganese-based layered oxide according to claim 3, characterized in that: The metal elements of the fifth period are selected from zirconium, niobium, molybdenum, ruthenium, tin, and antimony; the metal elements of the third period are selected from magnesium and aluminum; and the metal elements of the fourth period are selected from calcium, titanium, vanadium, chromium, nickel, iron, cobalt, copper, and zinc.

5. The high entropy doped manganese-based layered oxide according to claim 1, characterized in that: 0< a ≤0.04,0< b ≤0.04,0< c ≤0.04,0< d ≤0.04,0< e ≤0.04,0≤ f ≤0.04。 6. The high entropy doped manganese-based layered oxide according to claim 1, characterized in that: 0< a ≤0.03,0< b ≤0.03,0< c ≤0.03,0< d ≤0.03,0< e ≤0.03,0≤ f ≤0.03。 7. The high entropy doped manganese-based layered oxide according to claim 1, characterized in that: 0< a ≤0.02,0< b ≤0.02,0< c ≤0.02,0< d ≤0.02,0< e ≤0.02,0≤ f ≤0.02。 8. The high entropy doped manganese-based layered oxide according to claim 1, characterized in that: Said a , b , c , d , e , f At least 4 of the values ​​are less than or equal to 0.02 and greater than 0.

9. The high entropy doped manganese-based layered oxide according to any one of claims 1 to 8, characterized in that The doping element is selected from iron, nickel, copper, titanium, magnesium, zinc, antimony, tin, zirconium, aluminum, and niobium; And / or, the high entropy doped manganese-based layered oxide is a P2 and / or O'3 phase.

10. The high entropy doped manganese-based layered oxide according to any one of claims 1 to 8, characterized in that: The XRD diffraction pattern of the high entropy doped manganese-based layered oxide includes P2 phase diffraction peaks (002) (004) (100) (102); And / or, O´3 phase diffraction peaks are (001) (002) (200) (-111) (-202) (111).

11. A method for preparing a high entropy doped manganese-based layered oxide according to any one of claims 1 to 10, characterized in that the steps include: According to the chemical formula of the high entropy doped manganese-based layered oxide, sodium salt and manganese oxide in corresponding molar ratios, as well as the oxide of the doping element, are weighed and mixed to obtain a mixed powder; The mixed powder is pressed to obtain a pressed block; The block is sintered.

12. The preparation method according to claim 11, characterized in that: The sodium salt is selected from at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate and sodium nitrate; And / or, the mixing process includes ball milling, wherein the ball-to-material mass ratio is (5-20):1, the ball milling speed is 300-600 r / min, and the ball milling time is 3-24 h; And / or, in the pressing process, the steps specifically include: placing the mixed powder into a mold and pressing it under pressure to form a mold; And / or, in the sintering process, the sintering temperature is between 500 and 1100° C., the heating rate is between 3 and 20° C. / min, and the sintering time is between 1 and 24 hours.

13. The preparation method according to claim 12, characterized in that: The pressurized pressure is 5 to 30 MPa; And / or, the sintering temperature is between 800 and 1000°C.

14. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material comprises: the high entropy doped manganese-based layered oxide according to any one of claims 1 to 10; or the high entropy doped manganese-based layered oxide obtained by the preparation method according to any one of claims 11 to 13.

15. An electrode sheet, characterized in that: Comprising the sodium ion battery positive electrode material as claimed in claim 14.

16. A sodium ion battery, characterized in that: Comprising the sodium ion battery positive electrode material as claimed in claim 14, or, the electrode sheet as claimed in claim 15.

17. An electrical device, characterized in that: Comprising the sodium ion battery as claimed in claim 16.